Histology-agnostic approvals for antibody–drug conjugates in solid tumours: is the time ripe?. (August 2022) - Corti, Chiara; Antonarelli, Gabriele; Valenza, Carmine; Nicolò, Eleonora; Rugo, Hope; Cortés, Javier; Harbeck, Nadia; Carey, Lisa A.; Criscitiello, Carmen; Curigliano, Giuseppe
Abstract: Several antibody–drug conjugates (ADCs) have been recently approved to treat solid tumours. Since ADCs seem to have activity in multiple malignancies sharing the expression of a specific antigen, they may be mirroring the experience of histology-agnostic-targeted treatments. So, the possibility to interpret the activity of some ADCs across different cancer types in a biomarker-driven perspective arises. However, relevant biological, methodological, and regulatory challenges should be highlighted and addressed, in order to grant ADCs biomarker-driven regulatory approvals in the next future. In this review, we discuss challenges and opportunities posed by the pan-histological expansion of ADCs in solid tumours. In particular, we provide an overview about technological and manufacturing advancements; we offer up-to-date highlights of the current evidence from clinical trials investigating ADCs in solid tumours; we discuss the need for the identification of optimal predictive biomarkers, as well as major methodological, statistical, and regulatory considerations for a biomarker-driven histology-agnostic approach. Highlights: Several antibody–drug conjugates have been recently approved in solid cancers (84/85). ADCs seem to be active across histologies, sharing expression of a specific antigen (83/85). So, ADCs may be mirroring the experience of histology-agnostic targeted treatments (82/85). The pan-histological expansion of antibody–drug conjugates poses opportunities and challenges (73/85). Main issues are identification of predictive biomarkers and trial design optimisation (85/85).